Nonlinear Control Systems E-learning Course Support - Tapak, Peter (International Journal of Online and Biomedical Engineering (iJOE), 2013)
The paper presents the course on nonlinear control systems created in cooperation of the Institute of Control and Industrial Informatics of the Faculty of Electrical Engineering and Information Technology of the Slovak University of Technology in Bratislava with the Institute PRT/MI, Fernuniversitat in Hagen. The differences in real experiments utilization in the course considering distance and regular education are discussed.